Intercultural communicative competence and literary education in foreign language teaching - Sequeira, Rosa Maria (2022)
This essay aims to demonstrate the potential of literary text for promoting intercultural communicative competence in foreign language teaching. While literary education is often considered irrelevant nowadays, intercultural competence (or plurilingual and pluricultural competence, as it is described in the Common European Framework of Reference for Languages - CEFR) is the organizing principle of language curricula. However, the reading of literature presupposes the same kind of skills involved in intercultural competence, the same dialogic strategy, the same openness to alterity, the same tolerance of indetermination. Critical intercultural awareness is more than just the action-oriented approach seen in the CEFR; it is something that presupposes the ability to deal with more complex demands while maintaining a creative strength that should not be underestimated by any teaching. Literature - that intercultural text, par excellence – constitutes a useful methodological resource for intercultural competence that involve on-line communication, as well as new information and communication technologies.